Length-Weight Relationship, Size Distribution and Sexual Maturity of Climbing perch, Anabas testudineus (Bloch, 1792) From Different Habitats in Malaysia - Mohamad Jalilah; Victor Tosin Okomoda; Khor Waiho; Hidayah Manan; Hassan Anuar; Thumronk Amornsakun; Musa Nadirah (Tropical Life Sciences Research, 2026)
The growth and reproductive performance of fish are influenced by ecological factors. This study investigated the biology of the climbing perch, Anabas testudineus, in relation to habitat. A total of 2,880 climbing perch were collected from three habitats (irrigation canal, swamp and paddy field) in Peninsular Malaysia during the dry and rainy seasons, and their biometric measurements (total length and body weight) and sexual maturity indices were measured. Two-way Classification Analysis (TCA) revealed significant sexual dimorphism in all morphometric parameters, significant habitat effects on fish size, and pronounced seasonal variation in environmental parameters, while condition factor and seasonal effects on morphometrics were not significant. Results showed that body size was largest in fish from irrigation canals during the rainy season, with males averaging 12.84 ± 1.17 cm in total length (32.38 ± 4.4 g body weight) and females averaging 13.70 ± 1.83 cm (52.84 ± 12.54 g), consistent with the upper size range reported for this species. Fish from irrigation canals also exhibited more advanced gonadal development, confirmed by higher gonadosomatic indices (GSI) and histological evidence of vitellogenic oocytes in females and spermatozoa-filled seminiferous lobules in males. Principal Component Analysis (PCA) indicated that larger body sizes and advanced gonadal development were associated with higher dissolved oxygen and pH, whereas smaller sizes correlated with elevated water temperature. This study highlights the critical roles of sex, habitat quality and seasonal variation in shaping the growth and reproductive traits of wild climbing perch populations and provides evidence-based insights for fisheries management in tropical freshwater ecosystems.